Threshold voltage under white light illumination of zinc oxide based TFT in saturation regime - Mansouri, S.; Ben Mansour, N.; El Mir, L.; Al-Hartomy, Omar A.; Al Said, Said A. Farha; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Academic Press Ltd- Elsevier Science Ltd, 2013)
The zinc oxide thin film transistor was fabricated on a SiO2/Si substrate by sol gel method. Electrical characteristics of the zinc oxide transistor under various illuminations were analyzed. The apparent shifting in threshold voltage of zinc oxide transistor under light illumination was explained as a result of the superposition of a photo-generated current on the dark current overall biases. Our model has been confirmed by demonstrating that the apparent threshold voltages calculated under different illumination intensities are perfectly matched with the experimental results. The model indicates that there is a photo-current associated with the photo-excitation process in zinc oxide thin-film transistor and the apparent threshold voltage under illumination is not the intrinsic threshold voltage of a device as measured in the dark; instead, it is monotonically shifted from the intrinsic value due to the increase in photo-current. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Thin-Film Transistors; Organic Phototransistor; Room-Temperature; Zno; Channels; Layer